Major Determinants That Perform a Predominant Role Globally in the Furtherance of SMEs; ARDL and Bound Testing Approach - Khan, Ruby; Mihaisi, Sara Mohamed Kheir Ali (Future Science / FSH-PH Publications, 2022)
Purpose- Our study aims to empirically examine the influence of different economic indicators such as the global GDP growth rate and the global GDP per capita growth rate on the number of small and medium businesses (SMEs) around the world. In this article, we explored the challenges that SMEs face worldwide during the establishment process and various governments provide policies and regulations that promote and secure SME growth and development. Design/methodology/approach- This study presents a combination of time-series statistical analysis and analysis of literature gathered from published sources. A statistical analysis of the number of small and medium-sized businesses around the world is presented in the paper in relation to global GDP (current US dollars), global GDP growth rates (annual percent), and global GDP per capita (annual percent). Findings- Two determinants, Global GDP Growth rate and Global GDP Per Capita growth rate, are found as significant regressors. In addition, the number of SMEs worldwide during the previous year had a significant impact on the current year. Research limitations- limited availability of government sources of data are the biggest hindrance. In this study we relied on the statistics published by STATISTA, knowing that it’s a private company that maintains business statistics. Practical implications- SMEs have a significant impact on the economy that cannot be ignored. The government of some countries has commissioned a network of technology centers, tool rooms, and extension centers in collaboration with the private sector and foreign governments. These measures are a collective effort to support SMEs, preserve millions of jobs, and encourage domestic investments which will ultimately sustain the country's economic growth. Originality/value- In comparison with reviewed literature, this study focuses more on the regressors and regressands using statistical tools and the variables of interest.